Tracking Process and Benefit-Ability of Reflection Spectrum of TQM in Construction Industry - Hazem, Ryad T.; Hadi, Ali Hasan; Zamim, Salah Kh.; Chassib, Samir M. (Salehan Institute of Higher Education, 2025)
Total Quality Management is an important journey in developing the construction industries. Construction firms are working to achieve the aspirations of clients in terms of quality systems, and through adopting a total quality management tracking system, it contributes significantly to achieving the objectives of projects and aspirations of clients too. The primary objective of this research paper is to develop a tracking process for total quality management by identifying restrictions and a model of required actions to overcome these restrictions to ensure the successful implementation of TQM as a basic system in the construction industry. Therefore, the research is divided into two phases. The first phase included identifying and analyzing restrictions by using a questionnaire to survey 102 expert engineers in the construction industry and quality laboratories. The second phase involved developing the main hypothesis and analyzing required actions through analysis using the assumption of Kruskal-Wallis. The opinions of three groups of experts were also relied upon to complete this tracking phase. To evolve a tracking system that includes the actions that are coded in this research paper under (A-TQM). The proposed patch model carries the symbol (MPP) for tracking TQM and has been presented. The MPP consists of three figures that indicate the wheel of TQM, tracking of the required scope of TQM, and packages of scope to meet with TQM pillars.